Venous thromboembolism in metastatic urothelial carcinoma or variant histologies: incidence, associative factors, and effect on survival. (20th December 2016) - Ramos, Jorge D.; Casey, Martin F.; Crabb, Simon J.; Bamias, Aristotelis; Harshman, Lauren C.; Wong, Yu‐Ning; Bellmunt, Joaquim; De Giorgi, Ugo; Ladoire, Sylvain; Powles, Thomas; Pal, Sumanta K.; Niegisch, Guenter; et al.
Abstract: Venous thromboembolism (VTE) is common in cancer patients. However, little is known about VTE risk in metastatic urothelial carcinoma or variant histologies (UC/VH). We sought to characterize the incidence, associative factors, including whether various chemotherapy regimens portend different risk, and impact of VTE on survival in metastatic UC/VH patients. Patients diagnosed with metastatic UC/VH from 2000 to 2013 were included in this multicenter retrospective, international study from 29 academic institutions. Cumulative and 6‐month VTE incidence rates were determined. The association of first‐line chemotherapy (divided into six groups) and other baseline characteristics on VTE were analyzed. Each chemotherapy treatment group and statistically significant baseline clinical characteristics were assessed in a multivariate, competing‐risk regression model. VTE patients were matched to non‐VTE patients to determine the impact of VTE on overall survival. In all, 1762 patients were eligible for analysis. There were 144 (8.2%) and 90 (5.1%) events cumulative and within the first 6 months, respectively. VTE rates based on chemotherapy group demonstrated no statistical difference when gemcitabine/cisplatin was used as the comparator. Non‐urotheilal histology (SHR: 2.67; 95% CI: 1.72–4.16, P  < 0.001), moderate to severe renal dysfunction (SHR: 2.12; 95% CI: 1.26–3.59, P  = 0.005), and cardiovascular disease (CVD) or CVD risk factors (SHR: 2.27; 95% CI: 1.49–3.45, P  = 0.001) were associated with increased VTE rates. Overall survival was worse in patients with VTE (median 6.0 m vs. 10.2 m, P  < 0.001). Thus, in metastatic UC/VH patients, VTE is common and has a negative impact on survival. We identified multiple associated potential risk factors, although different chemotherapy regimens did not alter risk. Abstract : Venous thromboembolism is common and has a negative impact on survival in patients with metastatic urothelial tract cancers. Non‐urothelial histology, renal dysfunction, and the presence of cardiovascular disease or risk factors for cardiovascular disease increase a patient's risk for venous thromboembolism; however, there is no statistical difference in thrombotic risk between chemotherapy regimens.